Dampak Pembangunan Infrastruktur Digital bagi Pengembangan Bisnis: Systematic Literature Review - Tutus Wahyu Widagdo (Journal of Infrastructure Policy and Management (JIPM), 2023)
The development of information technology in this digital era certainly has an impact on various aspects. One of them influences business growth. Business activities are changing to become more dynamic without being hindered by space and distance in the digital era. So that business development becomes increasingly massive. One thing that influences business growth is the development of digital infrastructure. This research aims to determine the impact of digital infrastructure development and business development. The research method used is Systematic Literature Review (SLR) where a literature search is carried out using the main search terms, “digital infrastructure”, “business” and “business development”. This literature review has an important managerial impression for practitioners in developing business digitalization.